ANALISIS STRATEGI PEMASARAN JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) PADA USAHA DAGANG KENANGA DI KECAMATAN AMPENAN KOTA MATARAM - IDA AYU KETUT MARINI; IDA AYU NOPIARI; IDA BAGUS EKA ARTIKA (Universitas Mahasaraswati Mataram, 2019)
Micro, small, and medium enterprises (MSMEs) are one economic entity that continues to be encouraged by the government, because it can absorb labor, can reduce unemployment and also increase people's income This research is carried out at UD Kenanga, which produces and markets oyster mushrooms in the city of Mataram. This research is a descriptive study that aims to determine marketing strategies. This research is analyzed by SWOT analysis. The results show that UD Kenanga is strategically in quadrant II which shows that UD Kenanga is in a diversified strategy position. The conclusion of this study is the internal and external factors that influence the marketing strategy of white oyster mushrooms on UD. Kenanga consists of an affordable amount of capital, competent workforce, adequate product quality, strategic company location, competitive prices and able to produce their own seeds. Factors that become weaknesses are low production levels, not yet diversifying white oyster mushroom products, lack of a marketing system for white oyster mushroom products, limited production land, unprofessional financial management, no mushroom product promotion activities. Factors that become opportunities are broad market share, high purchasing power, government intervention, demand for oyster mushroom products is increasing, technological advances. Threatening factors are inter-company competition, changing seasons, consumer demands for quality mushroom products, rising fuel prices. Suggestions for companies, to diversify the company's products By diversifying products, so as to increase new customers or consumers. For the government, to pay more attention to the needs of micro businesses, especially to increase activities or technical training related to white oyster mushroom products.